Metabolism and Mental Illness - Sestan-Pesa, Matija; Horvath, Tamas L. (Trends in molecular medicine, 2016)
Over the past century, overwhelming evidence has emerged pointing to the hypothalamus of the central nervous system (CNS) as a crucial regulator of systemic control of metabolism, including appetite and feeding behavior. Appetite (or hunger) is a fundamental driver of survival, involving complex behaviors governed by various parts of the brain, including the cerebral cortex. Here, we provide an overview of basic metabolic principles affecting the CNS and discuss their relevance to physiological and pathological conditions of higher brain functions. These novel perspectives may well provide new insights into future research strategies to facilitate the development of novel therapies for treating mental illness. Hypothalamic neurons in the arcuate nucleus regulate feeding behavior and are modulated by a complex network of peripheral signals. Changes in feeding behavior and energy metabolism are common symptoms of mental illness and side effects of psychopharmacological treatment, indicating a possible connection between feeding and mental illness. Peripheral signals acting on hypothalamic neurons in the arcuate nucleus may help explain some of the molecular mechanisms by which feeding and mental health can be connected. In particular, serotonin signaling and metabolic pathways appear to be critical for such connections, as they are linked to both mental illness and feeding behavior.